The Analysis of Moral Values In "A Walk To Remember" Novel Written By Nicholas Sparks - Pratiwi, Dewi; Adrallisman, Adrallisman (e-LinguaTera, 2024)
This study aims at describing moral values of the main character dealing with life problems in ‘a walk to remember’ novel by Nicholas Sparks. This research is a qualitative descriptive study. The method of data collection is done by reading and recording techniques. The results showed: (1) there are three types of morality form, namely; moral value in human relations with God (faith and prayer), moral value in human relations with oneself (patience and sincerity), the manifestation of the relationship between humans and other human beings (parental advice to children, interpesonal advice, parental love for children , child affection for parents, affection between friend, and parent responsibility to children). (2) the moral of the main character is dealing with life problems are accepting the fate of God , being firm in stance, being submissive, working hard , praying to God, not being easily discouraged. Keywords: Moral, Value, Pragmatic, Manifestation.